Energetic costs regulated by cell mechanics and confinement are predictive of migration path during decision-making - Matthew R. Zanotelli (Nature Portfolio, 2019)
Migrating cells tune their energy utilization in response to their microenvironment, but how cellular energetics direct navigation remains unclear. Here, the authors report that energetic costs for motility, regulated by cell mechanics and confinement, predict the probability of migration choice.